Content analysis of tobacco content in UK television - Barker, Alexander; Whittamore, Kathy H.; Britton, John; Cranwell, Jo (BMJ Publishing Group, 2019)
Aims: Exposure to audio-visual tobacco content in media is a risk factor for smoking in young people. Whilst tobacco content in films has been extensively documented, content in mainstream television has received relatively little attention. We report an analysis of tobacco content in a sample of UK free-to-air prime-time television broadcasts in 2015, and compare this with a similar analysis from 2010. Design: Content analysis of all programmes and advertisements or trailers broadcast on the five national UK free-to-air channels in the UK between 6 and 10p.m. during three separate weeks in September, October and November 2015. Setting: Great Britain. Participants: None (media analysis only) Measurements: Occurrence of any tobacco, tobacco use, implied use, other tobacco reference/related objects and branding in every one-minute coding interval. Findings: Tobacco content occurred in 33% of all programmes and 8% of all adverts or programme trailer breaks. Actual tobacco use occurred in 12% of all programmes broadcast. Tobacco-related objects, primarily no-smoking signs, occurred in 2% of broadcasts; implied tobacco use and tobacco branding were also rare. The majority of tobacco content occurred before the 9p.m. watershed. Conclusions: These findings are virtually unchanged from our earlier analysis of programme content from 2010. Audio-visual tobacco content remains common in UK television programmes